Citespace-based visualization of nutritional research hotspots for oncology patients - Zhang, Na; Li, Mei; Zhao, Jing; Wang, Huijuan; Wang, Jingna; Niu, Honglin (Frontiers in Nutrition, 2026)
ObjectiveTo analyze the current status of nutrition-related research on cancer patients in the past 20 years, explore the current research hotspots and frontiers, and provide references for nutrition-related research on cancer patients.MethodsLiterature on cancer nutrition published between 1 January 2004 and 31 July 2024 was retrieved from the Web of Science Core Collection and the China National Knowledge Infrastructure (CNKI). CiteSpace 6.4. R1 was used for bibliometric analysis.ResultsFrom Web of Science, 954 English-language articles were included, yielding nine clusters: gastrointestinal neoplasms–enteral nutrition, nutritional screening and assessment (covering nutrition assessment, nutrition screening, and nutrition risk index), sarcopenia, nutritional prehabilitation, risk, advanced cancer, and patient-generated subjective global assessment. From CNKI, 1,156 Chinese-language articles were included, forming eight clusters: enteral/parenteral nutrition, relative angle, nurse-led interventions, nutritional support, prognostic nutritional index, patients with gastrointestinal tumors, enhanced recovery after surgery, and nutritional risk assessment. Research centered on gastrointestinal cancer and perioperative care, with hotspots in malnutrition screening and assessment, sarcopenia, enhanced recovery, and prognosis.ConclusionCancer nutrition research is progressing steadily, with a predominant focus on evaluating and screening patients’ nutritional status. Strengthening international and interdisciplinary collaboration and expanding the breadth and depth of inquiry will help advance this field.